Diagnostic Yield and Complication Rate of Stereotactic Biopsies in Precision Medicine of Gliomas - Katzendobler, Sophie; Do, Anna; Weller, Jonathan; Dorostkar, Mario M.; Albert, Nathalie L.; Forbrig, Robert; Niyazi, Maximilian; Egensperger, Rupert; Thon, Niklas; Tonn, Joerg Christian; Quach, Stefanie (Frontiers in Neurology, 2022)
Integrated diagnosis consisting of histology and molecular markers is the basis of the current WHO classification system of gliomas. In patients with suspected newly diagnosed or recurrent glioma, stereotactic biopsy is an alternative in cases in which microsurgical resection is deemed to be not safely feasible or indicated. In this retrospective study, we aimed to analyze both diagnostic accuracy and safety of a standardized biopsy technique. The institutional data base was screened for frame-based biopsy procedures. Only patients with a suspected diagnosis of glioma based on imaging were included. All tumors were classified according to the current WHO grading system. Clinical parameters, procedural complications, histology and molecular signature of the tissues obtained were assessed. Between 1/2016 and 3/2021, 1214 patients underwent a stereotactic biopsy: 617 (50.8%) for a newly diagnosed lesion and 597 (49.2%) for suspected recurrence. Median age was 56.9 years. MRI-guidance was used in 99.3% and additional PET-guidance in 34.3%. In total, stereotactic serial biopsy provided an integrated diagnosis in 96.3%. Most frequent diagnoses were IDH wildtype glioblastoma (n=596; 49.2%), oligodendroglioma grade 2 (n=109; 9.0%), astrocytoma grade 3 (n=108; 8.9%), oligodendroglioma grade 3 (n=76; 6.3%) and astrocytoma grade 2 (n=66; 5.4%). Determination was successful for IDH 1/2 mutation in 99.4%, for 1p/19q codeletion in 97.4%, for TERT mutation in 98.9% and for MGMT promoter methylation in 99.1%. Next generation sequencing was evaluable in 64/67 (95.5%) and DNA methylome analysis in 41/44 (93.2%) cases. 13 (1.1%) cases showed glial tumors that could not be further specified. 73 tumors were different non-glioma entities, e.g., of infectious or inflammatory nature. 75 out of 597 suspected recurrences turned out to be post-therapeutic changes only. The rate of post-procedural complications with clinical symptoms of CTCAE° 3 or higher was 1.2% over all patients and 2.6% in the subgroup of brainstem biopsies. There was no fatal outcome in the entire series. Image guided stereotactic serial biopsy allows to obtain histopathological and molecular diagnosis reliably with a very low complication rate even in tumors with critical localization. Thus, in patients not undergoing microsurgical resection this is a valuable tool for precision medicine of glioma patients.